2017
DOI: 10.2217/nnm-2017-0072
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive Solid Lipid Microparticles for Controlled Release of a Corticosteroid in the Chronic Obstructive Pulmonary Disease Treatment

Abstract: Aim: Therapeutic efficacy of pulmonary diseases is often limited and drug delivery systems offer new solutions to clinical problems. Solid lipid microparticles (SLMs) are suggested as systems for the delivery of therapeutics to the lung as, because of their size, they are able to deposit into secondary bronchi. Materials & methods: Here, we describe two novel different SLMs using chitosan and alginate such as mucoadhesive polymers and we also studied their biocompatibility and their effectiveness compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Increased numbers of circulating plasma EVs have been reported in various diseases, including systemic sclerosis [40], cardiovascular disease [21], thrombocythemia [22], type 2 diabetes mellitus [23], congenital heart disease [24], preeclampsia [25], COPD [41], and sepsis‐induced microvascular dysfunction, immunosuppression, and acute kidney injury [35]. We next asked if we could detect differences in plasma EV concentrations between the critically ill, non‐septic control, sepsis, and septic shock patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased numbers of circulating plasma EVs have been reported in various diseases, including systemic sclerosis [40], cardiovascular disease [21], thrombocythemia [22], type 2 diabetes mellitus [23], congenital heart disease [24], preeclampsia [25], COPD [41], and sepsis‐induced microvascular dysfunction, immunosuppression, and acute kidney injury [35]. We next asked if we could detect differences in plasma EV concentrations between the critically ill, non‐septic control, sepsis, and septic shock patients.…”
Section: Resultsmentioning
confidence: 99%
“…Ageing and age‐related diseases, i.e. cancer [57], idiopathic pulmonary fibrosis (IPF) [41], sepsis [36,58], Alzheimer's disease [59,60], are characterized by alterations in 5‐methycytosine content resulting in genome‐wide hypomethylation and promoter‐specific hypermethylation. In sepsis, many studies show that pathogen infection can increase DNMT activity, DNMT mRNA expression, and DNA methylation in epithelial [61,62], endothelial [54,63], and dendritic cells [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…SLNs are among the lipid nanocarriers developed for transporting the hydrophobic bioactive compounds with higher loading capacity along with the enhanced stability of the loaded bioactive compounds. [54][55][56][57][58][59][60] SLNs showed higher loading efficacy and bioavailability of various plant bioactive compounds like curcumin, resveratrol, quercetin, and catechin. These plant-derived bioactive compound-loaded SLNs showed higher potential in the prevention and cure of various chronic diseases.…”
Section: Slnsmentioning
confidence: 99%
“…On the other side particles with >10 µm diameter is suitable for deposition in the oropharynx. The microparticle in 1-5 µm size range is considered asanideal to achieve efficacious pulmonary deposition [39,40]. to deliver the microemulsion.…”
Section: Microparticlesmentioning
confidence: 99%
“…et al described alginate and chitosan-basedmucoadhesive solid lipid microparticles (SLMs) for the effective delivery of fluticasone propionate to treat chronic obstructive pulmonary diseases (COPDs). The developed SLMs were more effective in controlling oxidative stress-induced lung inflammation including ERK1/2 pathway activation and cigarette smoke extract-inducedsurvivin expression[39]. Lymphocyte-derivedmicroparticles (LMPs) stimulate oxidative stress in endothelial cells[41].Qiuet al(2014) identified that LMPs cause apoptosis of alveolar epithelial and bronchial cells by the activation of p38 mitogen-activated protein kinase signaling with an increase in cellular oxidative stress and arachidonic acid production[42].The first report on the expression of lung vascular endothelial growth factor in benzo(a)pyrenefed mouse model ofa lungtumour was published by Bandi and co-workers.…”
mentioning
confidence: 99%